2002
DOI: 10.1086/341889
|View full text |Cite
|
Sign up to set email alerts
|

The Amplitude of Magnetohydrodynamic Turbulence in the Inner Solar Wind

Abstract: Recent radio wave interplanetary scintillation observations have improved our knowledge of the level of turbulent fluctuations of plasma density in the inner solar wind at heliocentric distances of 16-26 R and less accurately outside this range. This information relates to fluctuations in the inertial subrange of the turbulence. Of particular concern in this paper is the heliocentric distance dependence of the power-law normalization parameter C 2 N . This measurement of C 2 N , when combined with independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
44
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 28 publications
(76 reference statements)
11
44
0
Order By: Relevance
“…deviation of the density turbulence in the fast solar wind at wavenumber k = 1.4 × 10 6 km −1 . The results for the slow solar wind density turbulence (Marsch & Tu, 1990;Woo et al, 1995) showed a constant level around 10 % which was also found in the later study from Spangler (2002). More recently Chen et al (2012Chen et al ( , 2013b have examined the slope of the density fluctuations power spectral density for 17 intervals of solar wind.…”
Section: Solar Wind Conditionssupporting
confidence: 64%
“…deviation of the density turbulence in the fast solar wind at wavenumber k = 1.4 × 10 6 km −1 . The results for the slow solar wind density turbulence (Marsch & Tu, 1990;Woo et al, 1995) showed a constant level around 10 % which was also found in the later study from Spangler (2002). More recently Chen et al (2012Chen et al ( , 2013b have examined the slope of the density fluctuations power spectral density for 17 intervals of solar wind.…”
Section: Solar Wind Conditionssupporting
confidence: 64%
“…F o rt h es o l a rw i n d ,α ∼ 11/3 agrees with that of Kolmogorov derived for fluid turbulence (Spangler & Sakurai, 1995;Spangler et al , 2002;Spangler , 2002;Tu & Marsch , 1994;Wohlmuth et al , 2001;Woo et al , 1995). The inner scale l i (which is also known as the dissipative scale) increases linearly with heliocentric distance as l i =(…”
Section: Electron Density Fluctuationssupporting
confidence: 82%
“…For a Kolmogorov spectrum with α = 11/3, this expression takes the form Spangler (2002). For the flat spectrum with α = 3, this becomes…”
Section: Electron Density Fluctuationsmentioning
confidence: 99%
“…Lee and Jokipii, 1975;Rickett, 1977;Coles and Harmon, 1989;Bastian, 1994;Cairns, 1998;Spangler, 2002] …”
Section: Density Turbulencementioning
confidence: 99%
“…[9] The empirical model we use for C N 2 (R) was originally mooted by Armstrong and Woo [1980] and later refined, based on VLBI observations between 10 and 50 R , by, for example, Spangler and Sakurai [1995] and Spangler [2002]:…”
Section: Density Turbulencementioning
confidence: 99%